ASPEK PEMBENTUK KAWASAN TRANSIT TERHADAP HIBRIDITAS KAWASAN STASIUN SOLOBALAPAN DAN TERMINAL TIRTONADI KOTA SURAKARTA - Prihatiningrum, Atik; Oktavallyan, Dwi Oktavallyan (Universitas Bengkulu, 2018)
Hybridity in the context of urban planning, connecting people and activities at points of more than one region with high-intensity movement through path affirmation and linking areas to create a city space with hybrid / cohesive compilations. No exception is the development of a compact transit area and support for transit activities, it needs to be linked with a pedestrianfriendly roadnetwork to local destinations in the form of commercial venues, workplaces, open spaces and housing with the effort to hybridize two transit areas in one more transit area development complexity. The result of research obtained by hybridity of staticun area of Solobalapan and Terminal of Tirtonadi at this time is high (score 5,5) with aspect of forming of transit area that has dominant impact on regional hybridity is diversity variable.